Internal audit and risk management practices among public universities in Malaysia - Wan Mustapha, Wan Musnida; Zainal Abidin, Nor Hafizah (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia, 2017)
This paper aims to explore the level of risk management practices in public universities in Malaysia and the role of internal audit in risk management practices. It is one of the few studies on risk management in public universities in emerging economies. It provides insights on changes in internal audit and risk management practices in public universities in response to external and internal forces on the Malaysian education sector. In gathering the perceptions of internal auditors on the subject matter studied, the questionnaire survey was distributed by hand to internal auditors at 20 Malaysian public universities. Due to the exploratory nature of the study, the responses were analysed using descriptive statistical analysis. The findings show that all Malaysian public universities have an internal audit unit, which is in line with the requirement of Treasury Circular Nos. 9/2004 and PS 3.1/2013. Two-thirds of the respondents are involved in evaluating the effectiveness of the risk management process. An older public university already achieved an advanced level with an established risk management practices.at. Meanwhile, majority of the newer public universities still have a basic or developing level of risk management practices.